EVALUASI PERENCANAAN DAN PENGANGGARAN PROGRAM PROMOTIF DAN PREVENTIF DINAS KESEHATAN KABUPATEN TANA TIDUNG, KALIMANTAN UTARA - Ranik Diastuti; Julita Hendrartini (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2020)
Background: Planning and budgeting are important components of community health efforts. Budget allocation for health in Tana Tidung was small. Budget absorption in health office was also low. Achievement of some Minimum Service Standard (SPM) indicators still below 60%. This indicates the possibility of problems regarding the quality of planning, budgeting, or implementation of promotive and preventive programs. Research needs to be done to evaluate the process of planning and budgeting of promotive and preventive program in Tana Tidung district health office. Objective: To evaluate the process of planning and budgeting of promotive and preventive program in Tana Tidung district health office to be known the obstacles of SPM indicators achievement. Methods: The type of research is case study research with single case design. Data collected by documentation document review, observation and in-depth interview with 17 employees in health of fice and primary healthcare centers during the period of March-April Data were analyzed with qualitative method. Results: Achievement of promotive and preventive program indicators in Tana Tidung district health office influenced by planning, either from human resources, data and information also guidelines for planning. Budgedting of promotive and preventive programs was ineffective and inefficient to improve achievement of SPM indicators. Constraints encountered are human resources have not been sufficient in quantity and quality, less communication, lack monitoring and evaluation functions, weak commitment of the programs holders in targets achievement, as well as the commitment of local authorities to promotive and preventive programs that are also weak. Conclusion: Planning and budgeting of promotive and preventive program had not been able to increase achievement of SPM indicators. Improvement is needed, especially on human resources, data management, policy components and also need a strong commitment to improve the achievement of promotive and preventive program indicators.